PERAN MAHASISWA DALAM MEMBANGITKAN MOTIVASI BELAJAR ANAK DI RANAH BATAHAN PASAMAN BARAT - Yuli Rohmiyati; Masnunah; Juaidah Agustina; Nurlida Asni; Zaianal Efendi Hasibuan (Ahsani Taqwim: Jurnal Pendidikan dan Keguruan, 2024)
Learning motivation is a key factor in improving individual learning outcomes. This article explains various strategies and factors that can help raise motivation to learn, including recognizing achievements, providing clear goals, creating a supportive learning environment, and using relevant and interesting learning approaches. Apart from that, this article also highlights the important role of parents, teachers and the social environment in shaping students' learning motivation. With a deep understanding of these factors, individuals can effectively increase their level of learning motivation, which in turn can lead to better learning outcomes and long-term success in education. In learning, of course, there are many obstacles that cause children's motivation to learn to decrease. As felt by the residents of Ranah Batahan West Pasaman, there are problems regarding learning, including: 1) Lack of guidance from parents, 2) Limited electronic media to support children's learning, 3) Lack of basic knowledge in education for children, 4) Lack of psychological aspects from within the child who helps in learning activities. In this case, the Field Work Lecture activity provides a tutoring program as the main program which aims to help with existing problems. The method used in this research is community education. All children who take part in tutoring can be helped in the learning process and develop motivation to learn. This can be seen from the enthusiasm and enthusiasm of the children who take part in learning activities.